Breastfeeding Self-Efficacy Among Parturient Women in Shanghai: A Cross-Sectional Study. (August 2019) - Li, Tengteng; Guo, Nafei; Jiang, Hui; Eldadah, Maher
Background: Breastfeeding self-efficacy has been shown to be a strong predictor of breastfeeding initiation and duration; however, factors associated with breastfeeding self-efficacy in China are unclear. Research aims: The aims were (a) to describe the breastfeeding self-efficacy of parturient women in Shanghai, China and (b) to identify the sociodemographic factors associated with mothers' breastfeeding self-efficacy. Methods: This is a cross-sectional retrospective descriptive study. Through convenience sampling, breastfeeding mothers ( N = 801) were recruited to assess breastfeeding self-efficacy before discharge from the hospital. Descriptive statistics were used to analyze the sociodemographic and perinatal characteristics, level of breastfeeding self-efficacy, and correlations between them. Results: In the process of breastfeeding, 52.2% ( n = 418) of participants encountered breastfeeding problems, 37.1% ( n = 297) perceived an insufficient milk supply, 82.4% ( n = 660) reported attending breastfeeding classes, but only 37.1% ( n = 297) chose exclusive breastfeeding. Chinese mothers reported a moderate level of breastfeeding self-efficacy, with an item mean score of 3.67 (score = 1–5). Whether or not encountering breastfeeding problems, infant feeding pattern (fully breastfeeding, partial breastfeeding, no breastfeeding) in the previous 24 hours, whether or not perceiving insufficient milk, and main caregiver's positive attitude toward breastfeeding (ranging from 1 to10, higher score indicating more positive attitude) were correlated with participants' breastfeeding self-efficacy score. (The correlation coefficients were −0.432, 0.377, −0.364, and 0.353, respectively.) Conclusion: The misperception of insufficient milk and main caregiver's attitude toward breastfeeding were important factors for breastfeeding self-efficacy. Greater efforts should be made during breastfeeding education and support.